VALIDITY AND RELIABILITY TEST OF THE INDONESIAN VERSION OF THE MULTIDIMENSIONAL SEXUAL SELF-CONCEPT QUESTIONNAIRE - Tiara Amalia Mentari; Haryanto; Lidia Hastuti; Imran (Nurse and Health)
Background: One comprehensive instrument for assessing different facets of sexual self-concept is the Multidimensional Sexual Self-Concept Questionnaire (MSSCQ). Its adaptation into different languages and cultural contexts is essential for cross-cultural research.